Tele-Psychiatry Assessment of Post-traumatic Stress Symptoms in 100 Patients With Bipolar Disorder During the COVID-19 Pandemic Social-Distancing Measures in Italy - Carmassi, Claudia; Bertelloni, Carlo Antonio; Dell'Oste, Valerio; Barberi, Filippo Maria; Maglio, Alessandra; Buccianelli, Beatrice; Cordone, Annalisa; Dell'Osso, Liliana (Frontiers in Psychiatry, 2020)
The acute phase of the COrona VIrus Disease-19 (COVID-19) emergency determined relevant stressful burdens in psychiatric patients, particularly those with chronic mental disorders such as bipolar disorder (BD), not only for the threat of being infected, but also for the strict lock-down and social-distancing measures adopted, the economic uncertainty and the limited possibilities to access psychiatric services. In this regards, telepsychiatry services represented a new important instrument that clinicians could adopt to monitor and support their patients. The aim of the present study was to investigate acute Post-Traumatic Stress Symptoms (PTSS) reported by patients with BD followed in the framework of a telepsychiatry service, set up in the acute phase of the COVID-19 outbreak at the psychiatric Clinic of the University of Pisa (Italy). A sample of 100 patients were consecutively enrolled and assessed by the IES-r, GAD-7, HAM-D and YMRS. Patients reported a mean (±SD) IES-r total score of 18.15±13.67. Further, 17% of the sample reported PTSS (IES-r > 32), 17% depressive symptoms (HAM-D > 17) and 26% anxiety symptoms (GAD-7 > 10). Work and financial difficulties related to the COVID-19 pandemic, and anxiety symptoms appeared to be positively associated with the development of acute PTSS. Acute manic symptoms appeared to be protective. The data of the present study suggest the relevance of monitoring patients with BD exposed to the burden related to the COVID-19 outbreak for prompt assessment and treatment of PTSS.